Instruments de politique publique en matière de réduction des émissions de gaz à effet de serre: transports urbains durables à Montréal et à Boston - Tremblay-Racicot, Fanny Rose (Université Laval, 2010)
Keywords: Transport en commun

L'eau prise aux mots: res communes ou marchandises? La participation de La Presse et du Devoir dans la construction d'une culture environnementale lors du débat sur la privatisation de l'eau au Québec de 1995 à 2005 - Vézina, Catherine (Université du Québec à Montréal, 2008)
Keywords: Devoir (Le); Presse (La)

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

Le transport des matières dangereuses dans l'est de Montréal: une analyse critique des projets d'investissement pour la rue Notre-Dame - Mezeguet Abellard, Jean (Université de Montréal, 2002)
Keywords: Rues

Savoirs, mobilisations et construction du risque environnemental de l'automobile durant les long sixties à Montréal - Poirier, Valérie (Université du Québec à Montréal, 2018)
Keywords: Automobile; Groupes populaires; Pollution

Les relations ville-port selon une approche d’écologie territoriale : le cas de Montréal - Jugie, Jeanne-Hélène (Université de Montréal, 2017)
Keywords: Navigation; Pollution; Port

The Machine in the Garden - Gibson, Andrew (Université Concordia, 2009)
Keywords: Automobile; Autoroutes; Banlieue

Les déterminants de la valeur dans le marché immobilier montréalais: étude appliquée aux lignes de distribution câblées, à la végétation et aux types de rue - Montpetit, Guillaume (Université du Québec à Montréal, 2010)
Keywords: Logement; Quartiers; Île-des-Soeurs

Exploration de l'articulation entre l'évaluation environnementale stratégique et l'étude des impacts sur l'environnement - Vallée, Lucie (Université du Québec à Montréal, 2003)

''L'autoroute est-ouest, c'est pas le progrès!'': environnement et mobilisation citoyenne en opposition au projet d'autoroute est-ouest à Montréal en 1971 - Poirier, Valérie (Bulletin d'histoire politique, 2015)
issued: 2015-24-00
Keywords: Autoroutes; Groupes populaires

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-23-00/2016-21-00

Légitimation du discours environnemental et conscientisation de l'opinion publique: l'expérience des militants de Greenpeace a Montréal - Meloche, Geneviève (Université du Québec à Montréal, 2000)
Keywords: Groupes populaires

Le biodôme de Montréal ou La nature médiatisée: patrimonialisation de l'environnement dans un dispositif d'immersion simulée - Crenn, Gaëlle (Université du Québec à Montréal, 2000)
Keywords: Patrimoine

The Dream of 'la ville fleurie': A Non-Linear History and Pragmatic Criticism of Public Gardens in Montreal - Despard, Erin (Université Concordia, 2013)
Keywords: Jardin botanique; Jardins; Île Notre-Dame